Penerapan Metode Role Playing untuk Meningkatkan Kemampuan Berbicara Siswa Kelas VI SD Negeri Wetan 01 Pagi (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
This study aimed to improve the speaking skills of sixth-grade students at SDN Negeri Kelapa Dua Wetan 01 Pagi in using the Simple Past Tense pattern (was/were) through the implementation of the Role Playing method. The research was conducted in two cycles involving 32 students as the subjects. The research method used was Classroom Action Research, consisting of the stages of planning, action implementation, observation, and reflection in each cycle. Data were collected through oral pre-tests and post-tests, as well as observations of students’ learning activities during the lessons. The results showed a significant improvement in students’ speaking skills. Their average score increased from 60.3 on the pre-test to 74.1 on the post-test. The percentage of students who achieved the Minimum Mastery Criteria also rose from 31% to 75%. The Role Playing method proved effective in enhancing students’ accuracy in using was/were, improving speaking fluency, and boosting self-confidence in oral communication. In conclusion, the application of the Role Playing method had a positive and significant impact on English learning outcomes among the sixth-grade students at SDN Negeri Kelapa Dua Wetan 01 Pagi. It is recommended that teachers continue to apply this method consistently, and that schools provide additional supporting facilities to optimize the learning process. For future studies, teachers and students are encouraged to expand the variety of role-play scenarios and include a control group to obtain a deeper and more comprehensive understanding of the effectiveness of the Role Playing method.